The Effect of Accountability, Public Trust, Reputation and Perceived Quality of Zakat Institution to Muzzaki’s Behavior - Raudhah Trisna Wardhani; Zaki Baridwan (The International Journal of Accounting and Business Society, 2023)
Purpose—This study aims to examine the effects of accountability, public trust, reputation, and the perceived quality of the institution on Muzzaki’s behavior. Design/methodology/approach — This study used an associative causality approach with data collection techniques using questionnaires. The population of this study were all muzzaki at the Zakat Management Organization in East Java, totaling 10,000 muzzaki. The sampling method used in this research was purposive sampling. The analysis technique used was a variance-based structural equation model (SEM) or component-based SEM, known as Partial Least Square (PLS). Findings—Institutional accountability had a positive effect on public trust, the institution's reputation, perceived quality, and Muzzaki’s behavior. Public trust had a positive effect on Muzzaki’s behavior, and the institution's reputation and perceived quality had a positive effect on Muzzaki's behavior. Practical implications — The results showed that the implementation of institutional accountability is an important factor in increasing public trust, institutional reputation, perceived quality, and muzzaki’s behavior, so the Amil Zakat Institution in East Java Province is expected to be able to implement accountability properly so that the level of public trust, institutional reputation and perceived quality will be increase, so does the behavior of muzzaki at the Amil Zakat Institution in East Java Province. Originality/value — This research replicates and modifies the concept of previous research where there was a gap between the similar variables studied, which obtained inconsistent results.